Adapting, Designing, and Evaluating EFL Resources: Establishing Criteria - Adi, Sugeng Susilo (Fakultas Ilmu Budaya, Universitas Brawijaya, 2012)
Teaching materials especially EFL learning resources are one of important components in language learning, besides other components such as teachers, learners, teaching methodology, and evaluation system. Teaching materials provide learners to get the language input or information which they need for their learning process. Because teaching materials take a very important role in the learning process, they should be appropriate for the learners. It means that there should be some criteria for effective materials which are used by a certain group of learners. This paper four general considerations for effective materials. In the first place, it is the consideration to the nature of the learner group, that deals with some principles such as: the materials should be appropriate for the learnersâ level of language development; the materials should challenge learners without frustrating them; and the materials should meet learnersâ immediate learning needs. This article also suggests that teaching materials should have twin aims: on the one hand they offer information and data about the language being studied, and in particular about the social context and culture within which communication takes place and derives much of its meaning and value.Keywords: learning resources, material development, design, criteria